2021
DOI: 10.3390/nu13041343
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone, a Dietary Bioactive Compound, Exerts Anti-Inflammatory Effects in Colitis by Stimulating Expression of the Colonic Epithelial PPAR-γ Transcription Factor

Abstract: Inflammatory bowel diseases (IBD) are chronic inflammatory disorders with increasing incidence and prevalence worldwide. Here, we investigated thymoquinone (TQ), a naturally occurring phytochemical present in Nigella sativa, for anti-inflammatory effects in colonic inflammation. To address this, we used in vivo (mice) and in vitro (HT-29 cells) models in this investigation. Our results showed that TQ treatment significantly reduced the disease activity index (DAI), myeloperoxidase (MPO) activity, and protected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Venkataraman et al [ 82 ] used thymoquinone, a bioactive molecule from the quinone-monoterpene family present in the volatile oil of Nigella sativa L. seeds, in a model of induced colitis. After treatment, there was a reduction in the expression of chemokine (C-X-C motif) ligand 1 (CXCL-1), IL-8, and COX-2, and an increased expression of PPAR-γ.…”
Section: Discussionmentioning
confidence: 99%
“…Venkataraman et al [ 82 ] used thymoquinone, a bioactive molecule from the quinone-monoterpene family present in the volatile oil of Nigella sativa L. seeds, in a model of induced colitis. After treatment, there was a reduction in the expression of chemokine (C-X-C motif) ligand 1 (CXCL-1), IL-8, and COX-2, and an increased expression of PPAR-γ.…”
Section: Discussionmentioning
confidence: 99%
“…CMV vectors were purchased from Promega (Cat# N1021 & N1101, Madison, WI, USA), and the PPRE-pNL1.3 plasmid was purchased from Addgene (Cat#84394, Watertown, MA, USA). Other reagents were obtained from the suppliers listed in our previous publication [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…The plasmid was extracted using the Plasmid Purification Maxiprep Kit (Cat# 12162, Qiagen, Germany) following the manufacturers' instructions. The plasmid DNA and Lipofectamine LTX mixture wer prepared in serum and antibiotic-free DMEM media as described previously [ 18 ]. The transient transfection with PPRE-pNL1.3 or pNL1.3 basic secreted luciferase reporter used as control.…”
Section: Methodsmentioning
confidence: 99%
“…In vivo, TQ significantly reduced the disease activity index (DAI) and myeloperoxidase (MPO) activity, protecting the internal microenvironment of the colon. In vitro experiments demonstrated that TQ mediates COX-2 expression and exerts anti-inflammatory function by inhibiting MAPK and NF-κB signaling [ 27 ]. In 2013, the relationship between TQ and COX-2 was verified in the skin of female HR-1 hairless mice.…”
Section: Tq Effect On Inflammationmentioning
confidence: 99%